Communication Through Social Media: Blogs and Wikis in Libraries - Vucenovic, Tamara (Qualitative and Quantitative Methods in Libraries, 2021)
:   Alexander Halavais wrote about blogging as a "free frame of reference" (2013: 109) and pointed to the fact that at the beginning of the 21st century there was a real "explosion" in the number of those who started writing in public. Most accepted the blogosphere as a space of freedom and democracy that provides us with opportunities to rethink the social order and our role and place in it. In this paper the importance of blogs being a turning point in publishing, is outlined, as well as the fact that users and their comments have quite important role in constituting the blogosphere. The openness of the blog is crucial for the interaction of authors and readers, "the border between the author and the reader is blurred or even lost, turning author in reader (comments on their blog) and readers in authors (comments on someone’s blog)" (Petrović, 2012).  Transition to online communication has inevitably led to changes, different, new "explosion" in the number of those who started writing/reading/communicating on the internet/in public. The paper outlines the ways in which librarians have turned to the dynamic environment of the blogosphere and the aim of this paper is to provide an outline of the possibilities that libraries have in order to improve communication with users by using blogs and wiki technologies. It would be briefly referred to the social media as a specific and valuable forum for librarians and an ideal place for spreading information and news, encouraging feedback and generating creative content.